A comparative study on phosphate removal from water using Phragmites australis biochars loaded with different metal oxides. Issue 6 (2nd June 2021) - Wang, Pengfei; Zhi, Mengmeng; Cui, Guannan; Chu, Zhaosheng; Wang, Shuhang
Abstract : Metal oxide-loaded biochars are a promising material to remove phosphate from polluted water to ultra-low concentrations. To facilitate preparing the metal oxide-loaded biochar with the best phosphate adsorption performance, five biochars loaded with Al, Ca, Fe, La and Mg oxides, respectively (Al-BC, Ca-BC, Fe-BC, La-BC and Mg-BC) were produced using Phragmites australis pretreated with 0.1 mol AlCl3, CaCl2, FeCl3, LaCl3 and MgCl2, respectively, characterized, and phosphate adsorption kinetics and isotherms of the biochars were determined. The maximum phosphate adsorption capacities ( Qm ) of the biochars ranked as Al-BC (219.87 mg g −1 ) > Mg-BC (112.45 mg g −1 ) > Ca-BC (81.46 mg g −1 ) > Fe-BC (46.61 mg g −1 ) > La-BC (38.93 mg g −1 ). The time to reach the adsorption equilibrium ranked as La-BC (1 h) < Ca-BC (12 h) < Mg-BC (24 h) = Fe-BC (24 h) <Al-BC (greater than 72 h). Qm of Ca-BC, Fe-BC, La-BC and Mg-BC depend on the molar content of metals in the biochars. The small phosphate adsorption rate of Al-BC is due to the slow intra-particle diffusion of phosphate attributed to the undeveloped porosity and dispersed distribution of AlOOH crystals on the Al-BC surface. Mg-BC is suggested for phosphate removal from water considering adsorption rate and capacity. Al-BC is applicable when a long contact time is allowed, e.g. as a capping material to immobilize phosphate in lake sediments.